2012
DOI: 10.1073/pnas.1212025109
|View full text |Cite
|
Sign up to set email alerts
|

Structure of RPE65 isomerase in a lipidic matrix reveals roles for phospholipids and iron in catalysis

Abstract: RPE65 is a key metalloenzyme responsible for maintaining visual function in vertebrates. Despite extensive research on this membrane-bound retinoid isomerase, fundamental questions regarding its enzymology remain unanswered. Here, we report the crystal structure of RPE65 in a membrane-like environment. These crystals, obtained from enzymatically active, nondelipidated protein, displayed an unusual packing arrangement wherein RPE65 is embedded in a lipid-detergent sheet. Structural differences between delipidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
75
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(88 citation statements)
references
References 70 publications
(75 reference statements)
10
75
0
Order By: Relevance
“…Interestingly, introduction of an extra nitrogen atom (QEA-G-001-NH 2 and QEA-G-002-NH 2 ) moderately recovered the inhibitory properties. This observation supports the previous hypothesis that the isomerization occurs via a carbocation intermediate, and that the positively charged compound inhibits the reaction (Golczak et al, 2005b;Kiser et al, 2009Kiser et al, , 2012Kiser et al, , 2014.…”
Section: Rdh8supporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, introduction of an extra nitrogen atom (QEA-G-001-NH 2 and QEA-G-002-NH 2 ) moderately recovered the inhibitory properties. This observation supports the previous hypothesis that the isomerization occurs via a carbocation intermediate, and that the positively charged compound inhibits the reaction (Golczak et al, 2005b;Kiser et al, 2009Kiser et al, , 2012Kiser et al, , 2014.…”
Section: Rdh8supporting
confidence: 91%
“…Although LRAT was shown to have a broad substrate specificity (Canada et al, 1990), chemical boundaries that determine the substrate selectivity for this enzyme had not been clarified. In contrast, the crystal structure of RPE65 was elucidated in detail (Kiser et al, 2009(Kiser et al, , 2012, revealing a narrow tunnel that leads into the active site of this enzyme. Indeed, a relatively small structural modification of the retinoid moiety could effectively abolish binding of an inhibitor to this enzyme.…”
Section: Resultsmentioning
confidence: 96%
“…Even though O 2 does not stoichiometrically participate in this proposed reaction, a major reduction in O 2 concentration, as accomplished by our deoxygenation procedure, should still greatly slow the rate of retinoid isomerization, which is not what we observed. The lack of activity reduction after deoxygenation also cannot be explained by potential tight binding of O 2 to the iron center as our prior structural and spectroscopic studies of RPE65 did not reveal such a stable Fe-O 2 complex (20,44). Most importantly, a recent structural determination of RPE65 in complex with a retinoid mimetic indicates that the polyene chain of carotenoids binds at a position distant from the iron center, which excludes formation of an Fe-O 2 -retinoid complex (26).…”
Section: Discussionmentioning
confidence: 78%
“…The typical yield was 3-6 mg of purified protein per liter of E. coli culture (Table 1). Our previous x-ray absorption spectroscopy studies on this asisolated sample suggested that the ACO catalytic iron was in the ferrous state (32). To confirm that the as-isolated sample obtained by our protocol was enzymatically active, we measured its steadystate kinetic parameters.…”
Section: Aco Purification and Enzymatic Analysis-mentioning
confidence: 99%